Stress differentially regulates synaptophysin and synaptotagmin expression in hippocampus - Thome, Johannes; Pesold, Brigitte; Baader, Miriam; Hu, Mei; Gewirtz, Jonathan C.; Duman, Ronald; Henn, Fritz A. (Biological psychiatry, 2001)
Background: In view of the effects of stress on synaptic plasticity, the regulation of synaptophysin and synaptotagmin expression by immobilization was analyzed by in situ hybridization. Methods: Rats were exposed to immobilization stress, which induced typical behavioral alterations, such as reduced locomotor activity after stress exposure. Determination of mRNA levels of the integral synaptic vesicle proteins was performed immediately after acute or chronic immobilization. Results: The results demonstrate that stress exposure leads to reduced expression of synaptophysin but increased expression of synaptotagmin in the hippocampus. Conclusions: This rapid and differential regulation of synaptic vesicle proteins could be responsible for some of the morphological, biochemical, and behavioral changes observed after stress exposure. These changes may be relevant to such clinical disorders as psychoses, depression, and posttraumatic stress disorder that are sensitive to stress and involve changes in neural and synaptic plasticity.
Gesehen am 09.11.2020